BLADDER EXTROPHY TREATMENT WITH PUBIC DIASTASIS CORRECTION IN AN ADOLESCENT. CLINICAL CASE - O.A. Malakhov; S.P. Yatsik; S.M. Sharkov; S.E. Trankovskiy; B.K. Shamov (Вопросы современной педиатрии)
Clinical case of bladder extrophy in an 11-years old girl. The presentation covers main pathogenic mechanisms of the disease, diagnostic algorithm and treatment approaches.Key words: Bladder extrophy, children. (Voprosy sovremennoi pediatrii — Current Pediatrics. — 2011; 10 (6): 198–203)